The Road to Bittersweet - Everhart, Donna (New York, NY : Kensington Books, 2018)
"Set in the Carolinas in the 1940s, a young woman reckons not just with the unforgiving landscape, but with the rocky emotional terrain that leads from innocence to wisdom as jealousy and betrayal threaten to accomplish what hardship never could--divide the family for good"-- Provided by publisher.
Keywords: Families -- Fiction; Sisters -- Fiction; Man-woman relationships -- Fiction; Mute persons -- Fiction; Savants (Savant syndrome) -- Fiction; South Carolina -- Fiction; Domestic fiction